A systematic review of cardiac rehabilitation registries. (October 2017) - Poffley, Alison; Thomas, Emma; Grace, Sherry L; Neubeck, Lis; Gallagher, Robyn; Niebauer, Josef; O'Neil, Adrienne
Introduction: Despite cardiac rehabilitation being recommended in clinical practice guidelines internationally these services are underutilised, programmes are not standardised and quality improvement methods and outcomes are rarely published. National registries are an important strategy to characterise service delivery, quality and outcomes, yet the number, type and components of national cardiac rehabilitation registries have not been reported. Aims: To identify and describe national and international cardiac rehabilitation registries, and summarise their key features. Methods: We systematically reviewed the literature reporting on cardiac rehabilitation registries at a national and international level. A search of four databases was conducted in July 2016, with two reviewers independently screening titles/abstracts and full texts for inclusion. Data were extracted from included studies, independently checked by a second reviewer and synthesised qualitatively. Results: Eleven articles were included in the review comprising seven national registries and one international registry (of 12 European countries) for a total sample of 265, 608 patients. Data were most commonly provided to the registry by a web-based application, and included individual-level data (i.e. sociodemographic characteristics, medical history, and clinical measurements). When reported, service-level data most commonly included wait times, programme enrolment and completion. The overarching governance, funding modes (e.g. industry ( n  = 2), government ( n  = 1)), and incentives for registry participation (e.g. benchmarking, financial reimbursement, or mandatory requirement) varied widely. Conclusion: The use of national and international registries for characterising cardiac rehabilitation and providing a benchmark for quality improvement is in its early stages but shows promise for national and global benchmarking.